Analysis of the current logistics and transport challenges in the context of the changing environment - Barysienė, Jurgita; Batarlienė, Nijolė; Bazaras, Darius; Čižiūnienė, Kristina; Griškevičienė, Daiva; Griškevičius, Algirdas J.; Lazauskas, Jonas; Mačiulis, Alminas; Palšaitis, Ramūnas; Vasiliauskas, Aidas V.; Vasilienė-Vasiliauskienė, Virgilija (Transport, 2015)
The rapidly changing world determines changes in the business processes. Logistics and transport are the areas facing constant changes. Therefore, an important point is to analyse the current problems of logistics and transport within the context of the changing environment. For many years, the experts of the Dept of Logistics and Transport Management of the Faculty of Transport Engineering from Vilnius Gediminas Technical University have been pursuing research both, in the Baltic Sea Region (BSR) in Lithuania and foreign countries. This research has been directed toward improvements to logistics and the entire supply chain in pursuit of economic, social and ecological competitiveness, an increase in the competitiveness and attractiveness of the transport system in the context of sustainable development, the impact of this system on the economic and social welfare of society, an increase in the competitiveness and attractiveness of the transport sector of improving the legal framework and the application of innovative technologies (including IT) in the transport sector aimed at implementing economic and social cohesion goals. The article deals with some of the key issues of the above introduced research.